2015
DOI: 10.1900/rds.2015.12.277
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determination of Serum Levels of Diabetes-Associated Adipokines

Abstract: ■ AbstractAdipose tissue secretes an abundance of proteins. Some of these proteins are known as adipokines and adipose-derived hormones which have been linked with metabolic disorders, including type 2 diabetes, and even with cancer. Variance in serum adipokine concentration is often closely associated with an increase (obesity) or decrease (lipodystrophy) in fat tissue mass, and it is affected by age, gender, and localization of the adipose tissue. However, there may be genetic variants which, in consequence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 187 publications
0
8
0
2
Order By: Relevance
“…It was also shown that the reactive centre loop (RCL) is flexible and located between G364 and P381. Unfortunately, the mechanism of action was not established, but it was shown that the most likely target for vaspin is the kallikrein-related peptidase 7 (hK7) [35,36]. The physiological functions of the vaspin target are diverse.…”
Section: Adipokinesmentioning
confidence: 99%
“…It was also shown that the reactive centre loop (RCL) is flexible and located between G364 and P381. Unfortunately, the mechanism of action was not established, but it was shown that the most likely target for vaspin is the kallikrein-related peptidase 7 (hK7) [35,36]. The physiological functions of the vaspin target are diverse.…”
Section: Adipokinesmentioning
confidence: 99%
“…Adipokiny (adipocytokiny) to białkowe substancje bioaktywne, wytwarzane przez adipocyty, komórki zrębu naczyniowego, komórki śródbłonka, pericyty, komórki prekursorowe tkanki tłuszczowej czy komórki układu odpornościowego [1,2,4,8].…”
Section: Adipokinyunclassified
“…Zaburzenie syntezy niektórych adipokin, np. leptyny, TNF-α, IL-6 czy rezystyny wiąże się z zapoczątkowaniem procesu kancerogenezy [8,14]. Inne adipokiny, jak np.…”
Section: Adipokinyunclassified
“…In obesity, accumulated fat tissue, depending on the current metabolic status, is characterized by a different secretory profile [ 2 , 3 ]. Among the recently identified regulatory peptides secreted by both adipose tissue and peripheral organs (mainly liver and skeletal muscle), which play an important role in the pathogenesis of metabolic changes in the course of obesity associated with type 2 diabetes, adropin, irisin, and vaspin play an important role [ 4 , 5 , 6 , 7 , 8 ]. The first of them, adropin , is a secreted peptide translated from the Energy Homeostasis Associated ( ENHO ) gene linked to metabolic control.…”
Section: Introductionmentioning
confidence: 99%